Analisis Kemampuan Matematika Dalam Pemecahan Masalah Termodinamika - Handayani Parinduri, Sri; Parinduri, Harianisyah (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2024)
The purpose of this study was to determine the role of math skills in thermodynamic problem solving. This type of research is qualitative using literature study survey research procedures and field studies. The subjects of this study were 5 students of the fifth semester of the Physics Tadris Study Program of UIN Sheikh Ali Hasan Ahmad Addary Padangsidimpuan in the 2024/2025 academic year. The results showed that math skills in thermodynamic problem solving are closely related. In order for students' thermodynamic problem solving skills to improve, good math skills are needed. Keyword: Math skills; problem solving; thermodynamics.